Un modèle intersectoriel de l’économie canadienne avec contrainte sur l’offre; une approche utilisant la programmation linéaire - Dale, P.; Dewaleyne, C.; Gigantes, T.; Hoffman, R. (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
This article describes a model, developed by the Structural Analysis Division of Statistics Canada, that helps analyse the economic implications of policy decisions in the environment of a supply-constrained economy. The Canadian input-output model is modified to introduce constraints on the uses of some commodity or industry products. These constraints take the form of limits on the availability of commodities for some uses, constraints that ensure that some minimum levels of final demand for each commodity are satisfied, and capacity constraints on the outputs of industries. Given these constraints, a linear function of the activity levels is maximized. The resulting solution gives a vector of activity levels, and also corresponding final demands that are optimal in terms of the objective function.The use of the model is illustrated by analyzing the 'optimal' allocation of industrial outputs in the face of a reduction in the availability of the commodity, 'crude mineral oils', for industrial uses. Two objective functions are used: total employment, and total wages, salaries and supplementary labour income. For each objective function, a ranking of the industries is defined by the solutions of the model.Experience with this model leads us to conclude that it is useful in indicating which industries are of primary interest in a specific shortage situation, rather than in setting exact values of cutbacks to impose on industries. In the conclusion, relaxation of the major assumptions underlying the model and some possible extensions are discussed.